ANALYSIS OF TRACE ELEMENT ATMOSPHERIC DEPOSITION BY BARBULA INDICA MOSS AT BAOLOC USING THE TOTAL REFLECTION X-RAY FLUORESCENCE TECHNIQUE - Nguyễn An Sơn; Đoàn Phan Thảo Tiên; Lê Hồng Khiêm; Nguyễn Thị Minh Sang; Nguyễn Thị Nguyệt Hà; Phạm Đăng Quyết; Nguyễn Đình Trung; Hồ Hữu Thắng; Nguyễn Trương Dương Cầm (Tạp chí Khoa học Đại học Đà Lạt, 2020)
In this investigation, the Total Reflection X-ray Fluorescence (TXRF) technique detected 24 elements: Al, P, S, Cl, K, Sr, Sc, Ti, Mn, Fe, Co, Cu, Zn, As, Br, Ba, La, Eu, Tb, Dy, Ta, Pb, Th, and U in Barbula indica moss collected at Baoloc (Vietnam) from November 2019 to March 2020. Factor analysis was used to explain contamination sources at the sampling sites. This study showed that the passive moss biomonitoring and TXRF techniques are efficient and very suitable for detecting trace elements due to atmospheric deposition in developing countries, especially Vietnam and some Asian countries.